Integrasi SIG dan CA–Markov Chain untuk Prediksi Perubahan Lokasi Rawan Banjir di Kabupaten Mamuju - Risma; Anugerah Putra, Ridha; Arham, Ihsan (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2025)
Climate change and the increasing frequency of extreme weather events have intensified the risk of hydrometeorological disasters, including flooding, particularly in regions experiencing rapid deforestation and land-use conversion. Mamuju Regency is one of the areas with high flood vulnerability due to its biophysical characteristics and accelerated land-use changes. This study aims to analyze the current flood susceptibility, predict land-use changes up to 2029 using the Cellular Automata–Markov Chain (CA–Markov) model, and assess how these changes influence future flood-prone areas. The research employs secondary datasets and Landsat satellite imagery, which were processed using Geographic Information Systems (GIS). Flood susceptibility analysis was conducted based on six key parameters—rainfall, slope, elevation, soil type, land use, and river proximity—each weighted using the Weighted Scoring method. The results indicate that in 2019, high-vulnerability areas covered approximately 279.84 km² and are projected to increase to 365.05 km² by 2029. This increase is primarily driven by declining forest cover and expanding built-up areas, which reduce infiltration capacity and intensify surface runoff. The predicted distribution of flood-prone areas shows that high-risk zones are concentrated in western Mamuju, particularly in rapidly developing subdistricts such as Kalukku and Mamuju. These findings highlight the need for stricter land-use control, enhanced watershed management, and spatially integrated flood mitigation strategies to reduce disaster risks in Mamuju Regency.